2022
DOI: 10.1002/jcph.1984
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Simulation Analysis of Less Frequent Nivolumab and Pembrolizumab Dosing: Pharmacoeconomic Rationale for Dose Deescalation

Abstract: Nivolumab and pembrolizumab, anti–programmed cell death protein 1 monoclonal antibodies, have revolutionized oncology but are expensive. Using an interventional pharmacoeconomic approach, these drugs can be administered less often to reduce costs and increase patient convenience while maintaining efficacy. Both drugs are good candidates for less frequent dosing because of long half‐lives and no evidence of a relationship of dose to efficacy. Established population pharmacokinetic models for both nivolumab and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…reducing the frequency) should be possible, without compromising outcomes. This is supported by simulation analyses for pembrolizumab and nivolumab (10).…”
Section: Introductionmentioning
confidence: 57%
“…reducing the frequency) should be possible, without compromising outcomes. This is supported by simulation analyses for pembrolizumab and nivolumab (10).…”
Section: Introductionmentioning
confidence: 57%
“…In terms of dosing intervals, prolonging the interval still maintains the pharmacodynamic parameters at effective levels. Simulated administration of nivolumab at 240mg Q4W/480mg Q8W regimen and pembrolizumab at 200mg Q6W regimen revealed that serum drug concentrations remained above the minimum effective concentration in more than 95% of patients ( 72 ). The Canadian Agency of Drugs and Technologies in Health simulated dosing regimens of pembrolizumab 4 mg/kg Q6W in patients weighing 70, 100, and 150 kg, all with trough target engagement above 97% ( 73 ).…”
Section: Dosing Regimen Optimizationmentioning
confidence: 99%
“…Considering the vastly increasing treatment cost using pembrolizumab and the financial burden among patients (in the Netherlands: € 29 million per year in 2016 versus €210 million per year in 2020), overdosing becomes even more highly undesirable ( 8 – 11 ). Alternative dosing strategies such as concentration-based dosing, dose banding, and weight-based dosing are suggested to be more cost-efficient than the current fixed-dose strategy ( 12 14 ). Therefore, it is vital to assess these alternative dosing strategies to lower the financial toxicity among patients being treated with pembrolizumab and warrant the accessibility of worldwide healthcare system.…”
Section: Introductionmentioning
confidence: 99%